Systemic Administration of α7-Nicotinic Acetylcholine Receptor Ligands Does Not Improve Renal Injury or Behavior in Mice With Advanced Systemic Lupus Erythematosus - Morales, Jessica Y.; Young-Stubbs, Cassandra M.; Shimoura, Caroline G.; Kem, William R.; Uteshev, Victor V.; Mathis, Keisa W. (Frontiers in Medicine, 2021)
There is a critical need for safe treatment options to control inflammation in patients with systemic lupus erythematosus (SLE) since the inflammation contributes to morbidity and mortality in advanced disease. Endogenous neuroimmune mechanisms like the cholinergic anti-inflammatory pathway can be targeted to modulate inflammation, but the ability to manipulate such pathways and reduce inflammation and end organ damage has not been fully explored in SLE. Positive allosteric modulators (PAM) are pharmacological agents that inhibit desensitization of the nicotinic acetylcholine receptor (7-nAChR), the main anti-inflammatory feature within the cholinergic anti-inflammatory pathway, and may augment α7-dependent cholinergic tone to generate therapeutic benefits in SLE. In the current study, we hypothesize that activating the cholinergic anti-inflammatory pathway at the level of the 7-nAChR with systemic administration of a partial agonist, GTS-21, and a PAM, PNU-120596, would reduce inflammation, eliminating the associated end organ damage in a mouse model of SLE with advanced disease. Further, we hypothesize that systemic α7 ligands will have central effects and improve behavioral deficits in SLE mice. Female control (NZW) and SLE mice (NZBWF1) were administered GTS-21 or PNU-120596 subcutaneously via minipumps for two weeks. We found that the increased plasma dsDNA autoantibodies, splenic and renal inflammation, renal injury and hypertension usually observed in SLE mice with advanced disease at 35 weeks of age were not altered by GTS-21 or PNU-120596. The anxiety-like behavior presented in SLE mice was also not improved by GTS-21 or PNU-120596. Although no significant beneficial effects of α7 ligands were observed in SLE mice at this advanced stage, we predict that targeting this receptor earlier in the pathogenesis of the disease may prove to be efficacious and should be addressed in future studies.